Determinants of Globalization and Growth Prospects for Sub-Saharan African Countries - Fofack, Hippolyte (2012)
Over the decades leading to the global financial crisis, the world witnessed a deepening integration of world economies, irrespective of a country s geographical location on the spherical space. This process of increasing interdependence of world economies, most notably illustrated by the scale of financial flows and movements of goods and services now termed globalization, has been facilitated by research and development and advances in technology, especially in the area of information and communication technology. In spite of its global nature, its expected benefits have not been uniformly distributed, however. This paper shows that the countries and regions that are driving the process of knowledge creation and production of high-tech and manufactured goods, building on frontier technology, are benefiting the most from globalization, increasingly acting as drivers and relegating Sub-Saharan Africa to the end-user status. In this process, the income gap between Sub-Saharan Africa and the globalizers has increased even more. However, the paper also shows that raising the level of technological endowment in Sub-Saharan Africa to that of developed countries could go a long way to bridge Africa's output gaps and improve its export performance in the new globalization landscape of the post-financial crisis era.